2014
DOI: 10.3168/jds.2013-7079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient temperature and sodium bicarbonate supplementation on water and electrolyte balances in dry and lactating Holstein cows

Abstract: The aim of this study was to quantify the effect of the interaction between 2 constant ambient temperatures [thermoneutrality (TN; 15°C) and high temperature (HT; 28°C)] and 2 levels of Na bicarbonate supplementation [calculated to provide diet Na contents of 0.20%DM (Na-) and 0.50%DM (Na+)] on water partitioning in dairy cows. Treatments were compared on 4 dry and 4mid-lactation Holstein cows according to 2 Latin squares (1 for each physiological stage) over the course of 4 periods of 15d. Diets consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
1
26
2
1
Order By: Relevance
“…The MK model offers the advantage to consider all changes in animal physiology simultaneously that are induced with increasing temperature (for an example see Fig. S6 in the Appendix, which shows that increasing transpiration, sweating and panting increases drinking water uptake and thus decreases the contribution of metabolic water to total water intake; the model results fit well to the data by Khelil-Arfa et al 63 , who quantified metabolic water to contribute about 5% under thermoneutral conditions (15 °C) and 4% under high-temperature (28 °C) conditions). A much larger effect of high temperatures as found in sub-tropical and tropical latitudes can be expected, however, from the differences in meteoric water, the difference in the diurnal adaptation of feeding and the differences in plant species composition.…”
Section: Discussionsupporting
confidence: 59%
“…The MK model offers the advantage to consider all changes in animal physiology simultaneously that are induced with increasing temperature (for an example see Fig. S6 in the Appendix, which shows that increasing transpiration, sweating and panting increases drinking water uptake and thus decreases the contribution of metabolic water to total water intake; the model results fit well to the data by Khelil-Arfa et al 63 , who quantified metabolic water to contribute about 5% under thermoneutral conditions (15 °C) and 4% under high-temperature (28 °C) conditions). A much larger effect of high temperatures as found in sub-tropical and tropical latitudes can be expected, however, from the differences in meteoric water, the difference in the diurnal adaptation of feeding and the differences in plant species composition.…”
Section: Discussionsupporting
confidence: 59%
“…1 Seif et al, 1973;Woodford et al, 1984;Silanikove et al, 1997;Osborne et al, 2002bOsborne et al, , 2009Kojima et al, 2005;Kume et al, 2010;Khelil-Arfa et al, 2014;Lamp et al, 2015. …”
mentioning
confidence: 99%
“…The authors reported that bicarbonate concentration of Bos taurus and Bos indicus heifers was significantly reduced during and after heat exposure (Beatty et al, 2006). Although Khelil-Arfa et al (2014) reported that TA did not affect concentration of bicarbonate, blood pH was significantly higher in heat exposed (28 °C; pH ≥ 7.35; P ≤ 0.001) lactating cows, compared with cows at thermoneutral (15 °C) conditions.…”
Section: Bicarbonatementioning
confidence: 93%
“…However Khelil-Arfa et al (2014) reported that TA did not affect concentration of bicarbonate, although blood pH was significantly higher in heat exposed (28 °C; pH ≥ 7.35; P ≤ 0.001) lactating cows, compared with cows at thermoneutral (15 °C) conditions. Conversely Beatty et al (2006) showed that bicarbonate concentration of Bos taurus and Bos indicus heifers was significantly reduced during and after heat exposure (≥ 32 °C, wet bulb temperature).…”
Section: Bicarbonatementioning
confidence: 98%